Historicism in university pedagogical disciplines - Victor V. Lobanov (Высшее образование в России)
This article represents the author’s work concerning the methods of teaching pedagogicaldisciplines based on profound studying of the historical material. It is suggested that encouraging students to learn historical process enables to raise the quality of university pedagogical education. This kind of knowledge is necessary for understanding the essence of innovations in contemporary Russian pedagogics.